WAKAF DAN PEMBANGUNAN EKONOMI - Ridwan, Murtadho (ZISWAF, 2017)
Waqf is one of Islam’s teachings that contain spiritual and material elements. Waqf is defined as something that is given for the usefulness of the people (as a charity) or for purposes related to Islam. This article aims to embrace the concept of waqf from the perspective of history, fiqh, and also macroeconomic perspective. The results show that waqf is one of Islamic teachings and also pre-Islamic teachings in providing their places of worship. From the fiqh perspective, fiqh scholars have explained the concept of waqf in the books of fiqh based on the al-Quran, the hadith and also their ijtihad. The concept of fiqh always undergoes development following the development of human reason. This is because the majority of waqf concepts are based on ijtihad which can change time and place. From the macroeconomic perspective, waqf property plays a role in building the necessary facilities of the community such as places of worship, educational institutions and also health centers. These facilities are believed to improve the quality of Human Resources (Sumber Daya Insani).